2018
DOI: 10.1002/jaba.524
|View full text |Cite
|
Sign up to set email alerts
|

A review of error correction procedures during instruction for children with developmental disabilities

Abstract: Error correction procedures are remedial strategies presented following an incorrect response that increases the probability that a correct response will occur in the future. Error correction is commonly used during skill acquisition programs for children with developmental disabilities; however, the specific strategy used may differ considerably. Recent comparative studies have examined the effect of numerous error correction procedures on the efficiency of acquisition for children with developmental disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…Despite an argument made against the use of a reinforcer during error correction to avoid prompt dependency (e.g., Greer & Ross, 2008;Yuan et al, 2019), both studies found including a reinforcement component did not reduce the effects of error correction. However, similar to Cariveau et al's (2019) review, these two studies also yielded inconsistent results in their comparisons. For example, while Yuan et al (2019) maintained that their results did not demonstrate a meaningful difference between the two arrangements, Carneiro et al (2019) reported a reinforcement component in error correction might, in fact, result in faster acquisition.…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…Despite an argument made against the use of a reinforcer during error correction to avoid prompt dependency (e.g., Greer & Ross, 2008;Yuan et al, 2019), both studies found including a reinforcement component did not reduce the effects of error correction. However, similar to Cariveau et al's (2019) review, these two studies also yielded inconsistent results in their comparisons. For example, while Yuan et al (2019) maintained that their results did not demonstrate a meaningful difference between the two arrangements, Carneiro et al (2019) reported a reinforcement component in error correction might, in fact, result in faster acquisition.…”
mentioning
confidence: 91%
“…Practitioners often further arrange a corrective procedure in case of errors. The most common error‐correction procedure is in the form of a remedial trial consisting of a prompt for a learner to perform the correct responses (e.g., Love, Carr, Almason, & Petursdottir, 2009), one or more correct responses from the learner (e.g., Cariveau, La Cruz Montilla, Gonzalez, & Ball, 2019; Pritchard & Malady, 2013), and sometimes a reinforcer (e.g., Carroll, Joachim, St. Peter, & Robinson, 2015; Yuan, Hua, & Zhu, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations